A review of biomarkers in the context of type 1 diabetes: Biological sensing for enhanced glucose control - Kelilah L. Wolkowicz; Eleonora M. Aiello; Eva Vargas; Hazhir Teymourian; Farshad Tehrani; Joseph Wang; Jordan E. Pinsker; Francis J. Doyle III; Mary‐Elizabeth Patti; Lori M. Laffel; Eyal Dassau (Wiley, 2021)
Abstract As wearable healthcare monitoring systems advance, there is immense potential for biological sensing to enhance the management of type 1 diabetes (T1D). The aim of this work is to describe the ongoing development of biomarker analytes in the context of T1D. Technological advances in transdermal biosensing offer remarkable opportunities to move from research laboratories to clinical point‐of‐care applications. In this review, a range of analytes, including glucose, insulin, glucagon, cortisol, lactate, epinephrine, and alcohol, as well as ketones such as beta‐hydroxybutyrate, will be evaluated to determine the current status and research direction of those analytes specifically relevant to T1D management, using both in‐vitro and on‐body detection. Understanding state‐of‐the‐art developments in biosensing technologies will aid in bridging the gap from bench‐to‐clinic T1D analyte measurement advancement.